Study of evolution and architecture of minimal introns - Faria, Luíza Zuvanov de (2020)
Eukaryotic introns show a wide span of size, from only 30bp to large 3.6Mbp. However, analysis of intron size distribution in diverse lineages shows a frequent accumulation of introns near the minimum size that is referred to as minimal introns. In this work, structure and evolution of minimal introns were studied based on diverse species of bilaterian animals, especially the platyhelminth Schistosoma mansoni and species from the Vertebrata phylum. Analysis of the distribution of introns size from Schistosoma mansoni shows a minimal intron peak at 34bp, a remarkably short size when compared to other eukaryotic species. Minimal introns from Schistosoma mansoni were preferentially found in some specific chromosomes. While studying intron retention (IR) and splicing signals, it was observed that premature termination codons (PTC) were preferentially found in the second and last codons of minimal introns due to contribution of the splice sites sequences. Symmetric minimal introns display the highest proportion of PTC-containing introns. We speculate that this observation reflects an evolutionary pressure associated with the fact that its retention does not shift the reading frame of translation. Interestingly, the proportion of PTC-containing introns does not increase with size in symmetric minimal introns as observed for non-symmetric minimal introns. We suggest that a large fraction of symmetric minimal introns that do not present PTC may be retained for the production of isoforms with few additional amino acid residues. The lack of preference of minimal introns with PTC for any position along the gene suggests that nonsense-mediated decay of Schistosoma mansoni is independent of exon junction complex (EJC). Study of the evolution of minimal introns from vertebrates shows that the acquisition of homeothermy had a great influence on minimal introns GC%. In high body temperature species, minimal introns can be divided into low and high GC% populations, with peaks of ~30% and ~70% respectively. Analysis of the human genome shows that, although the GC% variation was more prominent in minimal introns, the entire gene sequence varies. Genes without minimal introns do not appear to show GC% variation dependent on the body temperature. This suggests that minimal introns can serve as proxies for detecting temperature-responsive genes in humans. The transition from low to high GC% of some minimal introns may be impaired due to high IR levels in the intermediate GC%. Low GC% minimal intron-containing genes were related to cell division and thus transition to high GC% may be cumbersome due to high levels of IR. Furthermore, genes with low GC% minimal introns were observed to be related to oncogenic transformation and to be highly expressed in the meiosis process. Based on these results, we propose that minimal intron-containing genes could represent a new interesting system for studying diseases related to division defects, such as cancer and infertility. Also, as IR has been observed to be an important factor for selecting minimal introns GC%, the participation of minimal intron-containing genes in diseases in which increase of IR could be associated, such as diabetes type I and cancer, may be further explored.